2016
DOI: 10.3390/su8111194
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Weather Files on London Detached Residential Building Performance—Deterministic, Uncertainty, and Sensitivity Analysis on CIBSE TM48 and CIBSE TM49 Future Weather Variables Using CIBSE TM52 as Overheating Criteria

Abstract: Though uncertainties of input variables may have significant implications on building simulations, they are quite often not identified, quantified, or included in building simulations results. This paper considers climatic deterministic, uncertainty, and sensitivity analysis through a series of simulations using the CIBSE UKCIP02 future weather years, CIBSE TM48 for design summer years (DSYs), and the latest CIBSE TM49 DSY future weather data which incorporates the UKCP09 projections to evaluate the variance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In fact, the study shows that these two releases have shown no significant differences in assessing buildings' resiliency to climate change. For instance, overheating in present and future climatic scenarios employing both the CIBSE releases for all 14 UK locations sways little with similar findings in other published literature 16–18 . Even the absence of future high temporal resolution data with degree‐day and dynamic simulation methods predict heating demand within a few percentiles of one another while cooling demand was slightly varied due to the examined region's low yearly cooling requirement 19 .…”
Section: Factors Affecting Building Performancesupporting
confidence: 60%
See 1 more Smart Citation
“…In fact, the study shows that these two releases have shown no significant differences in assessing buildings' resiliency to climate change. For instance, overheating in present and future climatic scenarios employing both the CIBSE releases for all 14 UK locations sways little with similar findings in other published literature 16–18 . Even the absence of future high temporal resolution data with degree‐day and dynamic simulation methods predict heating demand within a few percentiles of one another while cooling demand was slightly varied due to the examined region's low yearly cooling requirement 19 .…”
Section: Factors Affecting Building Performancesupporting
confidence: 60%
“…Thus, For instance, overheating in present and future climatic scenarios employing both the CIBSE releases for all 14 UK locations sways little with similar findings in other published literature. [16][17][18] Even the absence of future high temporal resolution data with degree-day and dynamic simulation methods predict heating demand within a few percentiles of one another while cooling demand was slightly varied due to the examined region's low yearly cooling requirement. 19 Furthermore, the room temperature profile for a naturally ventilated office building is much worse than a predicted 2050s medium-high emission scenario.…”
Section: Indoor Overheating and Its Assessmentmentioning
confidence: 99%
“…A readily acceptable methodology should produce an output of weather datasets that is based on the currently used datasets and augment the use of standardized weather datasets for building energy simulation and thermal performance analysis [73]. Table A in Appendix D presents all 32 weather inputs with their units and probability distributions range for uncertainty and sensitivity.…”
Section: Stage 1 -Comparison Between Weather Parameters Used In the W...mentioning
confidence: 99%
“…This certification does not only have environmental benefits to it. It is also observed that having such certification increases the sale price, rent costs and occupancy premiums [10], along with the obvious benefits of saving operational energy costs and lower maintenance costs. The credits associated with green buildings LCA show a reduction of the material life cycle impacts as compared to the baseline model of the building.…”
Section: Leed Certificationmentioning
confidence: 99%